Urinary Tract Infection due to Extended-spectrum Beta-lactamase Producing Organisms is a Risk Factor for Bacteraemia Among Patients with Type 2 Diabetes Mellitus (Bangladesh Journal of Medicine, 2019)
Introduction: Urinary tract infection (UTI) is common among patients with diabetes mellitus and the aetiological agents are often extended-spectrum beta-lactamase (ESBL) producing bacteria. Diabetic patients with UTI are sometimes complicated by bacteraemia. This study was designed to evaluate whether UTI due to ESBL-positive organisms is a risk factor for bacteraemia among patients with type 2 diabetes mellitus.Methods: This was a cross-sectional analytical study, done in BIRDEM General Hospital, Dhaka, Bangladesh from January to April 2016. Adult (e”18 years) type 2 diabetic subjects of either sex with culture proven UTI were included in this study. All study participants were subjected to undergo blood cultures as well. ESBL-positivity of the infective organisms for UTI was evaluated as possible risk factor for bacteraemia.Results: Total patients were 145 including 119 (82%) females. Eshcerichia coli (112, 77.2%) was the most common aetiological agents followed by Klebsiella pneumoniae (28, 19.3%). In 54 (37.2%) patients UTI was due to ESBL-positive organisms. Ten (6.9%) patients were complicated by bacteraemia [7 (7/ 54, 13%) among patients with UTI due to ESBL-positive organisms and 3 (3/91, 3.3%) among patients with UTI due to non-ESBL organisms]. UTI due to ESBL-positive organisms appeared as a significant risk factor for bacteraemia (OR 4.37, 95% CI 1.08-17.38, p 0.03).Conclusion: Nearly two-fifths of UTI cases were due to ESBL-positive organisms in this study. ESBLpositivity of the causative organisms was a significant risk factor for bacteraemia among type 2 diabetic subjects.Bangladesh J Medicine Jan 2020; 31(1) : 9-12